Global climate change : implications for international public health policy - Campbell-Lendrum, Diarmid (2007)
Argues that the most effective public health responses to climate change are threefold viz. environmental management; surveillance and response aimed at safeguarding health from natural disasters and changes in infectious disease patterns; and, a more pro-active approach to ensure that development decisions serve the ultimate goal of improving human health.